2013
DOI: 10.1371/journal.pone.0054692
|View full text |Cite|
|
Sign up to set email alerts
|

Diabetes and Overexpression of proNGF Cause Retinal Neurodegeneration via Activation of RhoA Pathway

Abstract: Our previous studies showed positive correlation between accumulation of proNGF, activation of RhoA and neuronal death in diabetic models. Here, we examined the neuroprotective effects of selective inhibition of RhoA kinase in the diabetic rat retina and in a model that stably overexpressed the cleavage-resistance proNGF plasmid in the retina. Male Sprague-Dawley rats were rendered diabetic using streptozotosin or stably express cleavage-resistant proNGF plasmid. The neuroprotective effects of the intravitreal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 42 publications
(64 reference statements)
4
37
0
Order By: Relevance
“…The direct apoptotic effect of proNGF on RGCs delineates the apoptotic role of RhoA activation in retinal neurodegeneration. The significant activation of RhoA/p38 mitogen-activated protein kinase (MAPK) pathway causes neuronal death with increasing phosphorylation of c-Jun N-terminal kinase (JNK) and p38 MAPK in response to overexpression of proNGF in the diabetic rat retina (Al-Gayyar et al, 2013). …”
mentioning
confidence: 99%
“…The direct apoptotic effect of proNGF on RGCs delineates the apoptotic role of RhoA activation in retinal neurodegeneration. The significant activation of RhoA/p38 mitogen-activated protein kinase (MAPK) pathway causes neuronal death with increasing phosphorylation of c-Jun N-terminal kinase (JNK) and p38 MAPK in response to overexpression of proNGF in the diabetic rat retina (Al-Gayyar et al, 2013). …”
mentioning
confidence: 99%
“…In addition to alterations in TrkA function, expression of the p75 NTR receptor is increased in diabetic retinas, which combined with increased proNGF expression, favors activation of proapoptotic and proinflammatory pathways [30,32,33]. In the diabetic retina, this shift toward proNGF/p75 NTR signaling is accompanied by neurodegeneration, evidenced by death of RGC, vascular dysfunction and activation of RhoA/p38MAPK, a common pathway implicated in both neuronal death and vascular permeability [29,31,5459]. The action of proNGF/p75 NTR does not depend on additional factors present in the diabetic milieu, as evidenced by studies in which overexpression of cleavage-resistant proNGF, in otherwise healthy rodent retinas, causes increased neuronal cell death and vascular permeability [33,54,60].…”
Section: Prongf/ngf Imbalance In the Diabetic Retinamentioning
confidence: 99%
“…Our work demonstrated that proNGF-induced apoptosis in primary RGC cultures is accompanied by increased p75 NTR expression, and Rho kinase-dependent activation of RhoA, p38MAPK and JNK [54], all participants in apoptotic pathways downstream of the p75 NTR receptor [52,55,56,67,68]. Additionally, in both diabetic rats and in a rat model overexpressing proNGF, the p75 NTR receptor and apoptotic markers, cleaved poly (ADP-ribose) polymerase and caspase-3, are also increased in a Rho kinase-dependent manner [54]. Collectively, these results suggest a mechanism of retinal neurodegeneration triggered by proNGF/p75 NTR activation of RhoA and p38MAPK/JNK apoptotic pathways in RGC.…”
Section: Role Of Prongf/ngf In Retinal Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations